PERLINDUNGAN HUKUM TERHADAP DATA PRIBADI DALAM INDUSTRI FINANCIAL TECHNOLOGY - Pakpahan, Elvira Fitriyani; Chandra, Lionel Ricky; Dewa, Ananta Aria (Faculty of Law, Parahyangan Catholic University, 2020)
It came to the author’s attention that personal data collected or appropriated in the course of FinTech industry especially those that related to FinTech Peer to Peer Lending services are prone to misuse. The author, after perusing the prevailing laws regarding FinTech industry, concludes that a well-functioning system of rules has been put in place to regulate this industry. However, what is lacking is sufficient guarantee or protection of consumer’s personal data. Available is the option to use a weak (administrative, civil or penal) sanction against alleged misuse or misappropriation of personal data. To enhance better legal protection, the author suggests, that the government issue a special law on personal data protection, including establishing a a special governmental supervisory body to that purpose.